A Study to Quantify the Exercise Stress in Terms of Oxygen Consumption and Anaerobic Threshold in Patients of Suspected Coronary Artery Disease during Conventional Treadmill Testing - Lalitbhushan S. Waghmare; Tripti L. Waghmare; Ranjit Ambad (Journal of Pharmacy and Bioallied Sciences)
Background: Coronary artery disease (CAD) is one of the leading causes of mortality worldwide, and early detection is crucial for effective management. Exercise stress testing, particularly treadmill testing, is widely used to assess cardiovascular function, with oxygen consumption (VO2) and anaerobic threshold (AT) serving as key indicators of cardiovascular fitness and exertional capacity. The aim of this study is to quantify exercise stress using VO2 and AT in patients with suspected CAD during conventional treadmill testing. These parameters may provide additional insight into the severity of coronary artery blockages and help in predicting cardiovascular events. Objective: The objective of this study is to quantify the exercise stress in terms of oxygen consumption (VO2) and AT in patients with suspected CAD using conventional treadmill testing. Material and Method: The present study was conducted in the Department of Physiology at Jawaharlal Nehru Medical College Sawangi Meghe Wardha Maharashtra. The study included 100 patients with suspected CAD, aged 40 to 70 years. These patients presented with symptoms such as chest pain, breathlessness, or a family history of cardiovascular disease, prompting the need for exercise stress testing. A control group of 50 healthy individuals matched by age and sex was also included for comparison. Result: The study demonstrated that VO2 and AT levels significantly correlated with the presence and severity of CAD in patients. Patients with CAD exhibited lower VO2 levels and earlier onset of anaerobic threshold compared to the healthy control group. The results suggest that these parameters could be used as effective indicators in the early detection of CAD. Conclusion: The study highlights that measuring oxygen consumption and AT during treadmill testing can enhance the assessment of cardiovascular stress and provide valuable prognostic information in patients with suspected CAD.